Effect of nano-SiO2 on strength, shrinkage and cracking sensitivity of lightweight aggregate concrete. (30th June 2018) - Wang, X.F.; Huang, Y.J.; Wu, G.Y.; Fang, C.; Li, D.W.; Han, N.X.; Xing, F.
Highlights: The early compressive strength of LWAC was improved by adding nano-SiO2 . Nano-SiO2 had no significant influence on the long-term shrinkage of LWAC. With nano-SiO2 addition, LWAC reduces the cracking risk at the early age. The simplified models for the compressive strength and shrinkage are proposed. Abstract: This paper presents an experimental investigation on the effect of nano-SiO2 on the compressive strength, shrinkage and early cracking sensitivity of lightweight aggregate concrete (LWAC). Two types of ceramsite with different water absorption were used as lightweight aggregate in this study. LWAC with different nano-SiO2 dosage (1%, 2%, 3%) were compared with the reference LWAC to assess the effects of nano-SiO2 on LWAC. Results revealed that the incorporation of 3% nano-SiO2 increased compressive strength of LWAC significantly while the influence of nano-SiO2 on the long-term shrinkage of LWAC was not significant. The total cracking area was decreased with the increase in nano-SiO2 dosages from 1% to 3% by mass of the total binders at early age. The results of scanning electron microscopy (SEM) showed that the interfacial transition zone (ITZ) between lightweight aggregate and paste was enhanced with 3% nano-SiO2 addition. Subsequently, simplified models for compressive strength and shrinkage of LWAC were proposed and a comparison between the experimental data and models was discussed.